PENDEKATAN BARU DALAM PROSES TALAK DI INDONESIA: SEBUAH PESPEKTIF DARI ABDUL KARIM SOROUSH - Muhlasin, Muhlasin; Alimuddin, Khasan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM IBLAM), 2023)
This research is based on the practice of divorce conducted outside the Religious Court session. Such practices show that the birth of the Compilation of Islamic Law was not immediately accepted by the community. People still think that the rules contained in classical fiqh are final and irreplaceable. Therefore, this research aims to see that the renewal of Islamic law, especially divorce, is a necessity. This research is a library research (library research). The primary source of data in this research is Presidential Instruction Number 1 of 1991 concerning the Compilation of Islamic Law. The theory used to analyze the data is the theory of depreciation (al-Qabḍ) and development (al-Basṭ) popularized by Abdul Karim Soroush. The results of this study show that the mechanism of divorce before the Religious Court is a form of development of the rules contained in classical fiqh. Therefore, this mechanism cannot be said to be a form of desacralization of classical fiqh.